A New Species of Boehmeria Jacq. from North East India - Deb, D. B.; Dutta, R. (Indian Forester, 1964)
Boehmeria tirapensis Deb et Dutta spec. Nov. (Urticaceae) collected by the senior author from Tirap Frontier Division of North East Frontier Agency, India, is described with illustrations. The specific name is selected after the place of collection.